Analysis of DOAJ-Registered Open Access Journals in Asian Countries - Cho, Jane (International Journal of Knowledge Content Development & Technology, 2023)
This study aims to understand the characteristics of Asian OA journals and to identify differences by the countries. 3,103 DOAJ-registered OA journals from 21 Asian countries as of 2020 were selected and analyzed from various perspectives using correspondence and correlation analysis. The results revealed that Indonesia had the most DOAJ-registered open access journals, followed by Iran and India. An APC was not charged by 70% of journals, but this varied greatly by country. Meanwhile, as a result of comparing DOAJ-registered Asian journals with international citation database listed journals, 11% of journals were listed on Scopus and only 2.6% and 0.1% were listed on SCIE and SSCI, which is represents less than half of the global level. In addition, although there are many free to read local journals in China, Japan, and Korea, the number of OA journals registered in DOAJ is relatively small. Therefore, it is difficult to say that the progress of OA in local journals is fast even if the country’s global research competitiveness is high.